Organic Juice Processing Quality from the Processors’ Perspective: A Qualitative Study - Borghoff, Lisa Marie; Strassner, Carola; Herzig, Christian; Justus Liebig University Giessen (My University, 2023)
Organic food quality is based on processing. While the EU organic production regulation focuses on agricultural production, private standards provide more detailed information about further processing. For the development of organic processing, practitioner perspectives can provide valuable input. To get insight into practitioner perspectives, we conducted semi-structured expert interviews with nine employees of seven partly organic juice processing companies from Germany and Austria. Interview topics were (i) quality of organic juice processing in general, (ii) assessment of specific processing techniques, (iii) product quality of organic juice and (iv) flow of information between producer and consumer. We conducted a thematic analysis. We found that the experts’ understanding of process quality mostly includes more aspects than the EU organic production regulation. It covers the whole food chain plus aspects of social and environmental sustainability. The experts prefer directly bottled juice of local raw materials but chiefly accept juice made from concentrate of exotic raw materials because of environmental concerns. Organic juice is preferred when it is cloudy and natural fluctuations are interpreted as an indicator of natural quality. The experts report that consumer information is challenging because of low food literacy. Raising this might help reduce the number of processed juices on the market.
Keywords: organic food processing; organic food quality; juice processing; expert interviews; Germany; Austria; ProOrg; ddc:630